Mechanical properties and deformation twinning behavior of as-cast CoCrFeMnNi high-entropy alloy at low and high temperatures - Kim, Jeoung Han; Lim, Ka Ram; Won, Jong Woo; Na, Young Sang; Kim, Hyoung-Seop (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2018)
Tensile properties of an as-cast CoCrFeMnNi high-entropy alloy were investigated at various temperatures ranging from −160 to 1000°C. The tensile strength and ductility did not vary significantly with loading direction, despite the alloy’s strongly preferred crystallographic orientation. The impact toughness values of the as-cast high-entropy alloy were much higher than those of many traditional alloys, particularly at low temperatures. The mechanical properties of the as-cast high-entropy alloy were compared with those of wrought high-entropy alloy and noticeable differences between the two alloys were found. The maximum tensile ductility and three different strain hardening stages were observed at 500°C in the as-cast structure. Transmission electron microscopy observations demonstrated that the initiation of deformation twinning was very active even at 500°C. A simple calculation suggests that very large grains of the as-cast structure induced a reduction in twinning stress, retarding the onset of strain localization.